High-throughput amplicon sequencing of rRNA genes requires a copy number correction to accurately reflect the effects of management practices on soil nematode community structure - Darby, B. J.; Todd, Timothy C.; Herman, Michael A. (My University, 2014)
Nematodes are abundant consumers in grassland soils, but more sensitive and specific methods of enumeration are needed to improve our understanding of how different nematode species affect, and are affected by, ecosystem processes. High‐throughput amplicon sequencing is used to enumerate microbial and invertebrate communities at a high level of taxonomic resolution, but the method requires validation against traditional specimen‐based morphological identifications. To investigate the consistency between these approaches, we enumerated nematodes from a 25‐year field experiment using both morphological and molecular identification techniques in order to determine the long‐term effects of annual burning and nitrogen enrichment on soil nematode communities. Family‐level frequencies based on amplicon‐sequencing were not initially consistent with specimen‐based counts, but correction for differences in rRNA gene copy number using a genetic algorithm improved quantitative accuracy. Multivariate analysis of corrected sequence‐based abundances of nematode families was consistent with, but not identical to, analysis of specimen‐based counts. In both cases, herbivores, fungivores, and predator/omnivores generally were more abundant in burned than non‐burned plots, while bacterivores generally were more abundant in non-burned or nitrogen enriched plots. Discriminate analysis of sequence‐based abundances identified putative indicator species representing each trophic group. We conclude that high-throughput amplicon sequencing can be a valuable method for characterizing nematode communities at high taxonomic resolution as long as rRNA gene copy number variation is accounted for and accurate sequence databases are available.
Keywords: Tallgrass prairie; Nematodes; Konza prairie; Bar‐coding; Nitrogen enrichment; Burning